2019
DOI: 10.1002/pssb.201900394
|View full text |Cite
|
Sign up to set email alerts
|

Coercivity and Interactions in Sr–M Thin Films with Nonperpendicular Orientation

Abstract: Magnetic viscosity and interactions have been studied recently in bulk M‐type hexaferrites. Herein, this kind of study is extended to Sr–M (SrFe12O19) thin films deposited on SiO2/Si substrates using the pulsed laser ablation technique at relatively low substrate temperatures at 2.7 mbar oxygen atmosphere. Samples are characterized by X‐ray diffraction, scanning electron microscopy, and vibrating‐sample magnetometry. The high values of the coercive field (4.8 kOe) obtained for the films are in correspondence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In this expression, H a‐eff corresponds to the effective anisotropy field and χ o corresponds precisely to the initial susceptibility. With the values obtained for the saturation magnetization and fitting that initial part of the magnetization curve, a value of H a‐eff = 13 300 Oe was obtained and from this a value H c‐fit = 0.48 H a‐eff = 6400 Oe was calculated, for Bacop at 300 K. Note that it can also be expressed that H a‐eff = H a − N eff M s , and from here an effective N , ( N eff ), can be calculated using the value of the anisotropy field H a reported for BaM [ 16 ] and the experimental value obtained for saturation magnetization. Thus, a value of N eff = 10 was obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this expression, H a‐eff corresponds to the effective anisotropy field and χ o corresponds precisely to the initial susceptibility. With the values obtained for the saturation magnetization and fitting that initial part of the magnetization curve, a value of H a‐eff = 13 300 Oe was obtained and from this a value H c‐fit = 0.48 H a‐eff = 6400 Oe was calculated, for Bacop at 300 K. Note that it can also be expressed that H a‐eff = H a − N eff M s , and from here an effective N , ( N eff ), can be calculated using the value of the anisotropy field H a reported for BaM [ 16 ] and the experimental value obtained for saturation magnetization. Thus, a value of N eff = 10 was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13] Despite these novel properties, in M hexaferrites there are open issues associated to mechanisms of magnetization reversal and magnetic relaxation. [14][15][16] As the grain size is reduced and multidomain state becomes unfavorable, magnetization reversal must occur by coherent or incoherent processes and therefore aspects such as interparticle interactions come to be more important. In relation to that, a study on SrFe 12 O 19 (Sr-M) samples prepared using different methods was previously reported.…”
Section: Introductionmentioning
confidence: 99%